Manajemen Tata Kelola Dana Desa Sebagai Peningkatan Pembangunan Gampong Alue Naga Kecamatan Syiah Kuala Kota Banda Aceh - Sufyan; Tarmizi; Maimun (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2022)
Rural development in its implementation receives funds from the Regional Revenue and Expenditure Budget which is called the Allocation of Village Funds and the State Revenue and Expenditure Budget which is called the Village Fund. The characteristics of village development have a multidimensional nature concerning all aspects of community life in the village. The data analysis used was an analysis technique that was carried out throughout the research since the data collection began, data analysis was carried out continuously until the research report was prepared. Based on the results of the research, it was found that the government of Gampong Alue Naga, Syiah Kuala District, Banda Aceh had carried out a planning process in the context of managing gampong development as outlined in the Gampong Medium Term Development Plan (RPJMG) and in the Gampong Government Work Plan (RKPG) which became a reference in structuring the Budget. Gampong Income and Expenditure (APBG) using the Village Fund which is planned to involve the village community as a whole. In the process of organizing the gampong government formed an Activity Management Team (TPK) in managing village funds, involving all Human Resources (HR) owned in Alue Naga village, Syiah Kuala District, Banda Aceh. In the process of carrying out the development, the village government of Alue Naga involves workers from the community in general, and according to their respective expertise so that the work of development activities is carried out in accordance with the plans set out in the APBG.